Creating value from diverse knowledge in megaproject innovation ecosystems. Issue 6 (August 2022) - Jin, Zhizhou; Zeng, Saixing; Chen, Hongquan; Shi, Jonathan Jingsheng
Highlights: There is a curvilinear input-output relationship in megaproject innovation ecosystems. It results from the double effects of the increase in the size of knowledge base. It will be flattened as the relative search breadth of ecosystem peers increases. The synergy between ecosystem peers and the focal actor is revealed. Abstract: Although considerable emphasis has been placed on innovation in megaprojects research, it remains unclear how to obtain valuable outputs in megaproject innovation ecosystems. In view of the key role of knowledge in innovation activities, this study aims to explore the latent mechanism underlying the relationship between knowledge input and output quality, and how this relationship is impacted by ecosystem peers. We argue that there is an inverted U-shaped relationship between the size of knowledge base and the likelihood of high-quality output as a result of both the creation-potential effect and the integration-difficulty effect caused by the increase in knowledge base size. An empirical analysis of the Hong Kong-Zhuhai-Macao Bridge project confirms it and shows that the inverted U-shaped curve will be flattened as the relative search breadth of ecosystem peers increases. Our findings deepen the theoretical understanding of innovation activities in megaprojects, and provide new insights into co-creation in megaprojects innovation ecosystems.